Marketing 08/09 - Richardson John E. (American : McGraw -Hill, 2009)
This Thirtieth Edition of ANNUAL EDITIONS: MARKETING provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor?s resource guide with testing materials. USING ANNUAL EDITIONS IN THE CLASSROOM is offered as a practical guide for instructors. ANNUAL EDITIONS titles are supported by our student website, www.mhcls.com/online.
Keywords: Marketing; Marketing - Periodicals